Factors Affecting the Interest of Pregnant Women to Conduct PPIA Examination (Prevention of Mother-to-Child Transmission) in Senggreng Village, Sumberpucung District, Malang Regency - Suci Anggraeni; Atriyani Awaru (Universitas STRADA Indonesia, 2022)
Background: The government's policy that requires all pregnant women to undergo PPIA (Prevention of Mother-to-Child Transmission) examination is one of the prevention of HIV/AIDS and hepatitis transmission from mother to child, but PPIA (Prevention of Mother-to-Child Transmission) visits to pregnant women in Senggreng village are still low. Purpose: The purpose of this study was to analyze the factors that influence the interest of pregnant women in the PPIA (Prevention of Mother-to-Child Transmission) examination in Senggreng Village, Sumberpucung District, Malang Regency. Methods: The design of this research is quantitative with correlative analytic type. The population of this study were all third trimester pregnant women in Senggreng Village, as many as 31 people. By using the total sampling technique obtained a sample of 31 people. Analysis of the data used is multiple logistic regression. Results: The results showed that the parity factor with a value of p = 0.034 and the level of knowledge with a value of p = 0.040 had an effect on the interest of pregnant women in the PPIA (Prevention of Mother-to-Child Transmission) examination. And the dominant factor that influences the request for pregnant women in the PPIA (Prevention of Mother-to-Child Transmission) examination is the parity factor with the Exp(?) value of 6.153. Conclusion: Increasing the knowledge of pregnant women about the importance of PPIA (Prevention of Mother-to-Child Transmission) as well as accurate information related to the schedule for the implementation of the PPIA (Prevention of Mother-to-Child Transmission) examination should be improved. The cooperation of all parties, including cadres, families, and health workers, is needed to increase the achievement of PPIA(Prevention of Mother-to-Child Transmission) visits.